Implementasi Pengelolaan Sarana dan Prasarana Pendidikan dalam Upaya Meningkatkan Efektivitas Pembelajaran - Muhammad Ibnu Faruk Fauzi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
This study aims to analyze the implementation of the management of educational facilities and infrastructure and its contribution to increasing the effectiveness of learning at SMPI Darul Ulum Sangatta Utara. The research background is based on the importance of the role of facilities and infrastructure in supporting an optimal, effective, and meaningful learning process. This study uses a qualitative approach with a descriptive method, where data is obtained through observation, interviews, and documentation of school principals, teachers, and education staff. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the management of facilities and infrastructure at SMPI Darul Ulum Sangatta Utara has been carried out through five main stages, namely planning, procurement, utilization, maintenance, and evaluation. The implementation of this management is quite effective because it actively and continuously involves all school residents, especially in routine maintenance activities and the use of learning facilities. The existence of adequate facilities such as classrooms, laboratories, and information technology devices has been proven to increase student learning motivation and encourage the creation of a conducive learning atmosphere. However, some obstacles are still found, such as budget limitations and the need to update props that are no longer suitable for use. The implications of this study emphasize the importance of strategic planning and continuous evaluation in the management of facilities and infrastructure in order to continue to support the improvement of learning effectiveness, especially in the pesantren-based school environment.